Regenerasi dan Kaderisasi Kepemimpinan Kristen: Sebuah Studi Kasus - Bangngu, Hayma Elphis; Gunanto, Yohanes Edi (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
Regeneration and cadrerization are important programs that need to be done to progress an organization in the future. The existence of regeneration and cadrerization programs, both formally and informally, will help prospective leaders to be prepared both knowledgeably and mentally to become strong leaders and be responsible for their leadership calling. The research design used was case study qualitative research. Data were collected through interviews and questionnaires by the principal, vice principal, and senior teachers who have worked for more than three years and documentation studies. Data analysis was carried out with the stages of data reduction, data presentation, conclusion drawing, and verification. The results showed that the regeneration process has not been running optimally. Formal regeneration is not optimal because there is no Christian leadership training, so teachers as prospective leaders lack an understanding of Christian leadership. Informal regeneration has not been optimal because the principal has not provided intense guidance for teachers after the evaluation to help teachers develop and be prepared to become leaders.